Plant diversity influences plant volatile emission with varying effects at the species and community levels - Pamela Medina-van Berkum; Cynthia Albracht; Maximilian Bröcher; Marcel Dominik Solbach; Gideon Stein; Michael Bonkowski; François Buscot; Anna Heintz-Buschart; Anne Ebeling; Nico Eisenhauer; Tarek S. El-Madany; Yuanyuan Huang; et al. (Proceedings of the National Academy of Sciences, 2026)
Studies have investigated the interactions between plants through competition and resource sharing to understand the mechanisms behind the positive effects of plant diversity on productivity. Volatile organic compounds (VOCs) are important info-chemicals in plant–plant interactions, but they have so far rarely been considered in this context. Here, we measured VOC emissions at the community scale and for one species ( Plantago lanceolata ) in experimental plant communities of varying diversity (The Jena Experiment) to understand the role of VOCs in driving biodiversity-ecosystem functioning relationships. We show that plant diversity determines the release of plant VOCs at both scales. At the community level, plant species richness directly enhanced VOC emission and increased VOC richness both directly and indirectly by altering leaf area index. At the species level, plant diversity did not directly affect the VOC emissions of P. lanceolata but indirectly affected it by influencing the VOC emissions from the surrounding community. P. lanceolata individuals in communities with high concentrations of green leaf volatiles decreased their VOC emission, while those in communities with high concentrations of terpenoids increased their VOC diversity. Our results provide evidence that plant diversity shapes community-level plant VOC emission and thus influences focal plant VOC emission inside the community.